Hollywood bloodshed : violence in 1980s American cinema - Kendrick, James, 1974- (Southern Illinois University Press, 2009)
In Hollywood Bloodshed, James Kendrick presents a fascinating look into the political and ideological instabilities of the 1980s as studied through the lens of cinema violence. Kendrick uses in-depth case studies to reveal how dramatic changes in the film industry and its treatment of cinematic bloodshed during the Reagan era reflected shifting social tides as Hollywood struggled to find a balance between the lucrative necessity of screen violence and the rising surge of conservatism. As public opinion shifted toward the right and increasing emphasis was placed.